THE ADVANTAGES AND BARRIERS OF DYNAMIC ASSESSMENT IN EFL WRITING: A REVIEW - Dyah Fitri Mulati; Intan Mahardika Kusumastuti (Universitas Aisyah Pringsewu, 2023)
Assessment may affect the quality of teaching and learning. Dynamic Assessment (DA) is essential for teachers and students in education, especially in administering the assessment process. DA is a pedagogical approach grounded on Vygotsky's idea from the Zone of Proximal Development (ZPD). The key to such formation is the mediation session (by the teacher) and the automaticity or independency in performing the task (by the student) due to the appropriate guideline for administering the assessment. DA offers a more significant opportunity for future capabilities and experience to present and affords material about learning in general, including language learning. This paper presents an overview of DA in EFL Writing and its advantages and barriers in improving the quality of teaching with strategies to address. As the main results, this study revealed several advantages of using DA in EFL Writing and several barriers, including needing a precise procedure, taking more extended time, and more effort to implement. This paper is expected to contribute to developing teaching and learning quality, especially in assessing students in the EFL Writing context.